PEMBINAAN KESADARAN BERAGAMA REMAJA DI PANTI ASUHAN AISYIYAH AMPANG PADANG - Marlina, Desi; Hallen, Hallen; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
ABSTRACTThis research was motivated by the presence of some teenagers who likes orphanage neglect prayer and have poor morals against fellow residents Orphanage Aisyiyah Ampang Padang. The focus of this research are: (1) Fostering awareness of religion in adolescents who are at the Orphanage Aisyiyah Aisyiyah Ampang Padang in fostering teenage prayer (2) Development of religious awareness in young adolescents in foster morality. This study was conducted with a qualitative descriptive approach which describes the symptoms, facts and reality on the ground as it is about coaching teenagers in religious awareness Orphanage Aisyiyah Ampang Padang. Research informants are: Governing homes, juvenile homes, the instrument that I use in this study were interviews and observation. Techniques used in the processing of data through data reduction , data display and conclusion. The results obtained are praying coaching teenagers who are in orphanages Aisyiyah Ampang Padang include: Board immediately put into practice in their daily lives by using the method of example, habituation and invites. While the character development among adolescents: Board directly with in their daily practice how good morals to parents, by way of politeness towards fellow residents, foster mother, nursing administrators and also provide guidance to the juvenile home against mistakes in doing it.